Principios de marketing y competitividad como estrategias claves para el desarrollo de las MIPYMES en la provincia de El Oro - Maldonado, Ana Vanessa (2018)
Marketing and competitiveness are two key terms in the development of any type of economy, for this reason it is important to make an association between both, for which the application of a questionnaire was applied to 40 companies in the city of Machala. get very interesting results with respect to these two areas of study. On the one hand, the present study was carried out in companies from various sectors in order to have a somewhat more general perspective about the current market conditions, as well as the location of the organizations within the main cities of the province of El Oro. Another aspect that was taken into consideration is the fact of knowing whether or not companies have a professional person in charge of the marketing area, since this way you can guarantee a better application of the concepts in this area that you need to have present an organization to be able to stand out with greater force. It is important to emphasize that marketing is often consideredas a mere expenditure of advertising within organizations, especially if they are small or medium-sized, however with the passage of time that type of perspective has been changed and was able to identify the great contribution that it generates to the companies and their repercussions in the improvement of the competitiveness of the same ones, therefore the reflection of the present investigation that will be presented next will allow to know in an applied way the existing relation between the marketing and the competitiveness specifically focused on certain cities in the province of El Oro and the different standards or strategies that companies perform.